Crocin: Functional characteristics, extraction, food applications and efficacy against brain related disorders - Ali, Anwar; Yu, Liang; Kousar, Safura; Khalid, Waseem; Maqbool, Zahra; Aziz, Afifa; Arshad, Muhammad Sajid; Aadil, Rana Muhammad; Trif, Monica; Riaz, Sakhawat; Shaukat, Horia; Manzoor, Muhammad Faisal; et al. (Frontiers in Nutrition, 2022)
Crocin is a bioactive compound that naturally occurs in some medicinal plants, especially saffron and gardenia fruit. Different conventional and novel methods are used for its extraction. Due to some control conditions, recent methods such as ultrasonic extraction, supercritical fluid extraction, enzyme-associated extraction, microwave extraction, and pulsed electric field extraction are widely used because these methods give more yield and efficiency. Crocin is incorporated into different food products to make functional foods. However, it can also aid in the stability of food products. Due to its ability to protect against brain diseases, the demand for crocin has been rising in the pharmaceutical industry. It also contains antioxidant, anti-inflammatory, anticancer and antidepressant qualities. This review aims to describe crocin and its role in developing functional foods, extraction, and bioavailability in various brain-related diseases. The results of the literature strongly support the importance of crocin against various diseases and its use in making different functional foods.